INDICATIONS AND COMPLICATIONS OF HYSTERECTOMY IN MAIDUGURI, NORTHEASTERN NIGERIA - MB KAWUWA; AG MAIRIGA; BM AUDU (Ntec Specialist, 2001)
Objective: This study intends to determine the indications and complications of hysterectomy in a typical teaching hospital in tropical Africa and then to make appropriate recommendations. Setting, Materials and Methods: The records of 180 out of 240 patients who had hysterectomy over a ten year period (January 1989-December 1998) at the University of Maiduguri Teaching Hospital formed the basis of the study. Details of their mode of clinical presentation, indications for surgery and postoperative course and complications were extracted from their records and analysed. The SPSS statistical software package was used for the analysis of the data. Results: The mean age of the patients was 48.5 +/- 7.4 years with a range of 24 - 60 years and 66.6% aged 40 years and above. The mean parity among the patients was 4.3 +/- 3.7 with a range of 0 - 13. Thirty six (20%) were nulliparous. The indications for hysterectomy are uterine fibroids 114 (63.3%), utero vaginal prolapse 19(10.6%) and ovarian tumours 16 (8.9%). Dysfunctional uterine bleeding accounted for 2(1.1%) cases. There were 2 cases of ruptured uterus. One patient (0.6%) had endometrial cancer, while 2(1.1%) had atypical endometrial hyperplasia. Total abdominal hysterectomy, either alone or in combination with bilateral/unilateral oophorectomy and omentectomy, accounted for 160 (88.9%) cases. There was one case of subtotal hysterectomy from ruptured uterus following prolonged obstructed labour. Vaginal hysterectomy accounted for 19(10.6%) cases. The leading complications in this series are anaemia 34 (10.9%), abdominal wound dehiscence 20(11.1%), wound sepsis 14 (7.8%), febrile morbidity and post hysterectomy symptoms 12(6.7%). All cases of complete wound dehiscence occurred in association with abdominal hysterectomy. The type of incision and the level of experience of the surgeon (consultant and registrar) did not significantly affect the incidence of complications in this study. Conclusion: Uterine fibroids, uterovaginal prolapse and ovarian tumours are the leading indications for hysterectomy in our environment. Anaemia, abdominal wound dehiscence, sepsis and febrile morbidity are the commonest complications. Vaginal hysterectomy is associated with low treatment costs, shorter hospital stay and less morbidity when compared with abdominal hysterectomy. Therefore, whenever possible, vaginal hysterectomy should be done in preference to abdominal hysterectomy.